The Burden Effect Of Vitamin D Deficiency And Protective Effect Of Low & High Dose Of Vit D On Glycemic Control & Parotid Gland Function Of Diabetic Male Albino Rats (The Review of Diabetic Studies, 2025)
Background: Endocrine problems, including vitamin D insufficiency and diabetes mellitus, have been demonstrated to affect oral health by influencing the salivary glands.This study investigates the impact of these two disorders, both individually and in combination, on salivary glands in a rat model.Methods: A study examined the synergistic impact of vitamin D on dental cavity health, salivary gland function, and glycemic regulation in diabetic male albino rats. Fifty rats were allocated into five groups, each exposed to distinct diets and vitamin D concentrations, comprising a control group and multiple diabetes groups receiving low and high doses of vitamin D. Diabetes was produced using a single intraperitoneal dose of Streptozotocin, succeeded by a 12-week observation period. Blood samples were examined for glycemic levels and various biochemical indicators. Saliva collection and histological analysis of the salivary glands, tongue, and oral mucosa were performed to evaluate the impact of vitamin D on these tissues. The study sought to assess the overall effects of vitamin D deficiency and supplementation in a diabetic animal.Results: Significant biochemical differences were found, particularly in Group 3, which showed electrolyte imbalances and adverse lipid profiles. Inflammatory markers were highest in Group 3, while Vitamin D treatment (especially in Group 5) significantly reduced these markers and improved salivary gland histology. The findings indicate vitamin D as a crucial treatment for mitigating diabetes-related negative effects, enhancing both biochemical and tissue health in rats.Conclusion: The results underscore the significance of dosage and timing in Vitamin D supplementation for enhancing metabolic health in diabetes.